2014
DOI: 10.1007/s12262-014-1042-5
|View full text |Cite
|
Sign up to set email alerts
|

Two Etiological Reasons of Constipation: Anterior Rectocele and Internal Mucosal Intussusception

Abstract: Chronic constipation is a common problem in the general population. Rome III criteria can be used for the diagnosis of chronic constipation. The aim of this study is to emphasize the importance of anterior rectocele and mucosal intussusception as two etiological factors for chronic constipation. One hundred patients were included in this study after excluding other causes of the constipation by medical history, physical examination, and laboratory and radiological studies in 108 total patients who were admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Bozkurt et al . reported that rectocele is a risk of constipation 26 . Both diseases (constipation and rectocele) are likely to exhibit negative synergy with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Bozkurt et al . reported that rectocele is a risk of constipation 26 . Both diseases (constipation and rectocele) are likely to exhibit negative synergy with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Rectocele is a common diagnostic finding on defaecating proctogram in patients with OD and has been reported in up to 78% of symptomatic patients. 19 In our study, 52 (77.6%) patients were diagnosed with rectocele on clinicendoscopic assessment, with a sensitivity of 76.27% when correlated with proctogram results.…”
Section: Discussionmentioning
confidence: 53%
“…Rectocele is one of the most common causes of female ODS[ 21 , 22 ]. The reason for the high morbidity of rectocele might be that the internal anal sphincter is shorter and formed distally in the anterior upper anal canal, which might weaken the anorectal junction that is devoid of support structure in females[ 23 ].…”
Section: Discussionmentioning
confidence: 99%